Relações étnico-raciais na formação de psicólogas/os: uma análise dos projetos pedagógicos de três cursos de graduação em psicologia, de universidades públicas no estado de São Paulo - Macedo, Ana Beatriz (2024)
The present study aimed to analyze the approach to topics related to ethnic-racial relations in the training of psychologists based on the pedagogical projects of three undergraduate Psychology courses at public universities in the state of São Paulo. The Psychology course in Brazil was shaped under Eurocentric influence and colonial ideals. Despite the debates of recent decades around racial inequalities and the approval of policies aimed at racial equality and combating racism, such as Resolution CNE/CP 01/2004, which establishes the Curricular Guidelines for Education on Ethnic-Racial Relations (DCNERER), the structuring of content and the epistemological basis, as political decisions, still contribute to the reproduction and perpetuation of patterns related to coloniality. Studies show that the inclusion of studies on ethnic-racial relations can provide essential tools for an anti-racist approach in Brazilian Psychology, so curricula should address topics relevant to ethnic-racial relations. The methodology included a literature review and documentary analysis of the pedagogical course projects (PPC) of three selected public universities in the state of São Paulo. The analysis of the PPC allowed us to verify how the theme of ethnic-racial relations is present (or not) in the curricula of the Psychology courses of the institutions. It is concluded that, despite the weaknesses identified in the PPC regarding compliance with the DCNERER, we identified movements that suggest advances in the inclusion of the theme of ethnic-racial relations studies in their training curricula.